FLORA AND FAUNA PRESERVATION AND CONSERVATION ESSENTIAL TO SUSTAIN BIODIVERSITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 26 April 2016 – The Universiti Sains Malaysia (USM) School of Biological Sciences (PPSK) continues to promote the awareness on the preservation and conservation of the flora and fauna among its students with a visit to the Taiping Zoo & Night Safari and the Turtle Conservation and Information Centre, in Pasir Panjang, Segari, Perak recently.